FAKTOR PENYEBAB INEFEKTIVITAS FUNGSI TERMINAL BANDAR RAYA PAYUNG SEKAKI (BRPS) KOTA PEKANBARU - suryaningsih, suryaningsih (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2016)
Public sector management is the responsibility of local governments as managers of public facilities in the region. Terminal as one of the public facilities in the area has a function that is vital for the development of a city. Terminal has a very important role, but there are still many terminals that exist in regions throughout Indonesia are not running effectively. One such ineffective terminal is Type A terminals in Pekanbaru City. This paper discusses the factors causing inefectivity function of Bandar Raya Payung Sekaki terminal (BRPS) Pekanbaru City. The purpose of this study is to describe and analyze factors causing the inefectivity function of Bandar Raya Payung Sekaki terminal (BRPS) Pekanbaru City. The method used in this research is qualitative descriptive by using interview technique, observation, and documentation as a tool for data collection in the field. Result of research indicate that there are 3 main factors causing inefektivitas terminal of Bandar Raya Payung Sekaki (BRPS) that is, policy factor, environment social factor (spatial, security, and accessibility), and institutional factor.